Of forests and fields : Mexican labor in the Pacific Northwest - Sifuentez, Mario Jimenez, 1979- (Rutgers University Press, 2016)
"Of Forest and Fields tells the story of the ethnic Mexicans that toiled in the fields, canneries, packing sheds, and forests who helped turn the Pacific Northwest into one of the most productive agricultural regions in the country. The book explores the struggle of Braceros, Tejanos, and Mexican immigrants, to contest their exploitation in various ways. The history of their resistance culminated in the creation of one of the most important farm worker's unions in the country, the Pineros y Campesinos Unidos Noreste (PCUN)"--Provided by publisher
Keywords: PCUN -- History.; PCUN; Migrant agricultural laborers -- Northwest, Pacific -- History.; Foreign workers, Mexican -- Northwest, Pacific -- History.; Mexican Americans -- Northwest, Pacific -- History.; Mexicans -- Northwest, Pacific -- History.; Immigrants -- Northwest, Pacific -- History.; Working class -- Northwest, Pacific -- History.; Agricultural laborers -- Labor unions -- Northwest, Pacific -- History.; Northwest, Pacific -- Economic conditions.; Northwest, Pacific -- Ethnic relations.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies.; Agricultural laborers -- Labor unions; Economic history; Ethnic relations; Foreign workers, Mexican; Immigrants; Mexican Americans; Mexicans; Migrant agricultural laborers; Working class; Pacific Northwest; History